A Human-Centered Design Approach in Developing the “Jejak Cilik” Parenting App Prototype - Maricar, M. Azman; Fauziawan, Affan Irfan; Medhiatika, Ni Luh Made Vinaya; Juliantari, Ni Luh Putu Shinta; Putra, I Made Dwipa Aditya; Karang, Komang Lazuardi Edo (Sistemasi: Jurnal Sistem Informasi, 2025)
Developmental disorders in early childhood are a critical issue requiring serious attention. The role of parents in stimulating and monitoring child development is crucial; however, challenges remain, such as limited understanding and access to relevant information. To address this problem, this study developed a parenting app prototype called Jejak Cilik using a Human-Centered Design (HCD) approach. The development process followed four key phases: Discover, Define, Design, and Prototype & Test. The prototype was evaluated using heuristic evaluation with severity ratings to identify interface and user experience (UI/UX) issues. In addition, completion and duration metrics were assessed to evaluate the success rate and time required to complete assigned tasks. The heuristic evaluation, involving three evaluators, revealed three aspects that required immediate improvement and four aspects categorized as low-priority issues. Meanwhile, the completion and duration metrics, tested by 20 participants, showed promising results: all tasks were successfully completed by all users, with an average task completion time of less than one minute. However, during implementation, several issues were encountered that hindered task execution. Based on the findings from both evaluations, the prototype requires further refinement to enhance overall user experience.